Spatiotemporal dynamics of coastal aquaculture and driving force analysis in Southeastern China - Zimin Ying (Taylor & Francis Group, 2020)
Introduction: Large-scale disordered coastal aquaculture development causes severe environmental problems. However, quantitative assessments of spatiotemporal dynamics and driving factors for coastal aquaculture are essential and urgent for coastal aquaculture sustainability.Outcomes:Using remote sensing products and geographic information science, we investigated the long-term landscape changes due to coastal aquaculture, and explored its underlying driving factors in the Ningde coastal region, Southeastern China. Results show that coastal aquaculture area increased from 90.65 km2 in 2003 to 96.08 km2 in 2016, and its structure underwent tremendous changes. The area of artificial shrimp ponds increased by 496.15% and the area of farmland ponds decreased by 25.81% between 2003 and 2016. In addition, we revealed that from 2003 to 2016, the change trends of the coastal aquaculture area and the entire Ningde coastal region were consistent, and became more fragmented and dispersive. Furthermore, regression results indicate that the growth and attenuation of coastal aquaculture areas were significantly affected by the initial coastal aquaculture area in 2003. Discussion and Conclusion:To sustainably manage the coastal ecosystems, we provide several recommendations (e.g., a coupled human and natural systems approach to understanding human-nature interactions, integrated assessment, and systematical spatial planning and monitoring) for future research and management.